2013
DOI: 10.3928/01477447-20130327-12
|View full text |Cite
|
Sign up to set email alerts
|

Novel Method for Ensuring Leg Length in Total Hip Arthroplasty

Abstract: Despite the overwhelming clinical success of total hip arthroplasty, complications such as leg-length discrepancy can be a significant cause of functional impairment and patient dissatisfaction. Multiple intraoperative techniques are available for measuring femoral limb length; however, many require additional invasive hardware and those that do not are less accurate at measuring limb length. This article introduces a novel, noninvasive intraoperative technique that quickly and accurately measures limb length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These methods can be divided into four main categories: (1) Based on the preoperative templating to define the correct neck cut, the correct neck length of the femoral component (in case of a modular head) or the correct depth of insertion of the femoral component (by measuring the distance of the tip of the greater trochanter to the shoulder of the femoral component),5678 (2) based on the usage of a standard pelvic reference point and of a femoral reference point, and measurement of the distance of these two points as the limb length changes intraoperatively [the marking of the pelvic reference point and the measurement can be performed with the aid of calipers,91011121314151617 bented K-wire,18 suture (tied in the skin, in a K-wire, or in a pin),19 Steinman pin in the infracotyloid groove or screw above the superior acetabular rim,2021 (3) based on clinical tests intraoperatively such as the shuck test, the drop kick test, and the leg-to-leg comparison,152223 and (4) based on navigation system's measurements 16242526. In addition, some other techniques have been described, such as measuring the gap between the tenotomy limb edges of the abductor musculotendinous insertion on the greater trochanter15 or evaluating the level of the center of the head in relation to the tip of the greater trochanter with the aid of a plate in a femoral head slot 27…”
Section: Discussionmentioning
confidence: 99%
“…These methods can be divided into four main categories: (1) Based on the preoperative templating to define the correct neck cut, the correct neck length of the femoral component (in case of a modular head) or the correct depth of insertion of the femoral component (by measuring the distance of the tip of the greater trochanter to the shoulder of the femoral component),5678 (2) based on the usage of a standard pelvic reference point and of a femoral reference point, and measurement of the distance of these two points as the limb length changes intraoperatively [the marking of the pelvic reference point and the measurement can be performed with the aid of calipers,91011121314151617 bented K-wire,18 suture (tied in the skin, in a K-wire, or in a pin),19 Steinman pin in the infracotyloid groove or screw above the superior acetabular rim,2021 (3) based on clinical tests intraoperatively such as the shuck test, the drop kick test, and the leg-to-leg comparison,152223 and (4) based on navigation system's measurements 16242526. In addition, some other techniques have been described, such as measuring the gap between the tenotomy limb edges of the abductor musculotendinous insertion on the greater trochanter15 or evaluating the level of the center of the head in relation to the tip of the greater trochanter with the aid of a plate in a femoral head slot 27…”
Section: Discussionmentioning
confidence: 99%
“…The fuzzy concept of ne anatomical parameter indices has increased the error rate of surgeries and postoperative complications. Maratt et al [4] conducted a follow-up study of 120 post-THA patients in 2012 and found that 30% of patients had unequal lower limb lengths, poor hip joint function, and some experienced limping symptoms.…”
Section: Introductionmentioning
confidence: 99%